2015
DOI: 10.1088/0268-1242/30/8/085022
|View full text |Cite
|
Sign up to set email alerts
|

Migration of noble gas atoms in interaction with vacancies in silicon

Abstract: First principles calculations in combination with the nudged elastic band method have been performed in order to determine the mobility properties of various noble gas species (He, Ne, Ar, Kr, and Xe) in silicon, a model semiconducting material. We focussed on single impurity, in interstitial configuration or forming a complex with a mono-or a di-vacancy, since the latter are known to be present and to play a key role in the formation of extended defects like bubbles or platelets. We determined several migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Other possible interactions concern Si interstitials and He atoms. Previous investigations showed that the interaction between helium interstitials in silicon is weak and can be safely neglected [20]. We also assume that the combined aggregation of helium and Si interstitials does not play a significant role in the formation of helium bubbles.…”
Section: A3 I-i Interactionsmentioning
confidence: 89%
See 2 more Smart Citations
“…Other possible interactions concern Si interstitials and He atoms. Previous investigations showed that the interaction between helium interstitials in silicon is weak and can be safely neglected [20]. We also assume that the combined aggregation of helium and Si interstitials does not play a significant role in the formation of helium bubbles.…”
Section: A3 I-i Interactionsmentioning
confidence: 89%
“…After 22 ps, the decrease of the amount of V n seen in figure 1(d), is correlated to the increase of V n He p clusters, and is obviously due to the transformation of V n to V n He p by capturing one or more He atoms. A single helium atom is indeed less mobile than V 1 , with a migration energy of 0.68 eV [20], but enough to diffuse during the short MD time span. In contrast with V n , the mean size of V n He p aggregates continuously increases during the simulation.…”
Section: A Typical Scenariomentioning
confidence: 97%
See 1 more Smart Citation
“…In semiconductors, fewer works are available, and typically focus on helium in silicon or in silicon carbide. Theoretical investigations revealed that in the undefected cubic diamond lattice, an interstitial helium atom is located in tetrahedral sites and diffuses through hexagonal sites . It has also been shown that helium interstitials do not easily cluster , thus highlighting the pivotal role of vacancies in the initial stages of helium bubbles formation.…”
Section: Introductionmentioning
confidence: 99%